Diagnostic expression of the cotton pink bollworm Pectinophora gossypiella (Saunders) Ace1 exposed to some insecticide by the real-time PCR - Diab, Hanan Salah El-Din Taha (International Research Journal of Insect Sciences, 2023)
The Pink Bollworm Pectinophora gossypiella (Saunders) is a devastating pest in Egyptian cotton field. Insecticide control failure may be happen due to its biological features of hide inside bolls and rarely exposed to insecticide application. Thus, a bulk of bolls infested with larvae collected from fields of Sharkia and Benysuef governorate. Moreover, exposed to py, Op sub lethal concentrations in laboratory bioassay. Toxicity features as LC50, LC90 and the slope, and RR was completed. Whereas the common target site of OP and pyrethroid is the acetylcholinesterase enzyme. Thus, the gene Ace1 encoding AChE relative expression was investigated using molecular marker of real-time PCR procedures via the steps of generating data was RNA isolation and characterization, cDNA synthesis, then generating normalization factors, and Ct data attained and analyzed using 2-ΔΔCT method to quantify the gene expression quantitatively of insecticide treated larvae tissue extracted. Data showed the most expressed ratio of samples was cypermethrin followed by deltamethrin compared with the control and the least was malathion and chlorpyrifos, thus, the most effective insecticide was malathion and the least were cypermethrin according to ct values. Hierarchical clustering combined with Heat map and principle component analysis based on various clustering systems and algorithm as distance measures were completed. Validation of reference gene in addition to gene expression stability analyzed by the three optimal gene finders and showed that deltamethrin and cypermethrin treated genes having lower mean weights and considered transcriptionally stable and ideal reference genes.